Testicular Torsion; Plea for Urgent Exploration - Yovich, John L (Archives of Clinical and Medical Case Reports, 2020)
A case of misdiagnosis of testicular torsion in a 17-year old virginal boy is presented. Orchidectomy of a gangrenous testis was required following an 11 hour uncomfortable flight from London to Mumbai. The wrong diagnosis of epididymitis and a misleading scrotal ultrasound contributed to the delayed surgery and loss of testis.